Public Attitudes towards the Government’s Policy Communication in Preventing COVID-19 - Abrar Adhani; Akhyar Anshori; Ananda Mahardika (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
The spread of COVID-19 in Indonesia needs the policy to overcome it, especially for the implemented communication. The government communicates that dealing with the spread of COVID-19 is a problem in society. The study is to find out how the public’s response is related to the communication of government policies in preventing COVID-19. The approach of this study is quantitative, with data collection carried out through questionnaires for 400 respondents. The data obtained are analyzed using SPSS 25.0. The study finds that the government conducted communication crises dealing with the overcoming of COVID-19 to protect their policies from the reality that society’s policies were not obeyed. This attitude happens due to the inconsistency of government officers and their conduct towards society. Related to the vaccination of COVID-19, the majority of society in Medan says they agree with the program to prevent the spread of COVID-19.